Strategic Cost of Diversification - Lyandres, Evgeny (Review of Financial Studies, 2007)
This article proposes a new explanation for the large cross-sectional variation in the excess values of diversified firms. The model applies the idea of shareholders’ limited liability affecting firms ’ output market strategies to the analysis of financial and operating choices of conglomerates. The inability of conglomerates to commit to unconstrained optimal operating strategies, following from the lack of flexibility in choosing their divisions ’ capital structures, reduces their value. Thus, the model highlights a new type of inefficiency of the conglomerate organizational structure, which is suboptimal financing. The predictions of the model are generally supported by the data. (JEL G32, G34, L13) The valuation of diversified firms (conglomerates) that operate divisions in multiple industries has attracted significant attention in recent years. Early evidence suggests that conglomerates are discounted, on average, relative to their single-division rivals (e.g., Lang and Stulz (1994), Berger and Ofek (1995), Lins and Servaes (1999), and Klein (2001)). More recent studies show that carefully controlling for the endogeneity of the decision